Validation of WHO-IMNCI Algorithm for Jaundice in 0-2 Months Aged Infants at Tertiary Level Hospital - Kanodia, Piush; Mahaseth, Sameer; Paranjuli, Vishnu (Journal of Nepalgunj Medical College, 2020)
Introduction: For the effective management of these major childhood illnesses, WHO and UNICEF have developed the “Integrated Management of Neonatal and Childhood Illness” (IMNCI) Strategy. Aims: The aim of study is to evaluate the utility of the WHO/ UNICEF algorithm for Integrated Management of Neonatal and Childhood Illness (IMNCI) for jaundice up to two months of age. Methods: This is Prospective observational comparative study. Total of 300 subjects were taken from Emergency and Outpatient Department of Pediatrics. The treatment steps were identified as according to the ‘Assess and Classify’ module of IMNCI algorithm. All relevant investigations were performed, using appropriate methods. Blood sugar was done in all recruited children and serum bilirubin levels were done in all infants presented with jaundice. Based on this detailed clinical evaluation and relevant investigations, final diagnosis were made and therapies were given. These diagnosis and treatments were considered as the ‘Gold Standard’ for comparison. Results: There were 300 young infants, of whom 162(54%) were male and 138(46%) were female infants. Total of 146 infants were admitted, 24 from OPD and 122 from Emergency. 154 infants were sent home after initial management in hospital. Severe jaundice was present in 24 infants according to IMNCI and 12 infants according to Gold Standard in 0-2 months of age. The predictive utility of algorithm for the diagnosis of severe jaundice with a sensitivity of 100%, specificity of 75%, positive predictive value of 50% and negative predictive value of 100% in 0-2 months of age group. Conclusion: Algorithm performed well in identifying severe jaundice with the sensitivity of 100% and specificity of 95%.